УЮШМАГАН ЁШЛАР ҚАТЛАМИНИ ЎРГАНИШДА ИЖТИМОИЙ ТАДҚИҚОТЛАРДАН ФОЙДАЛАНИШ - Исмаилова, Ш.К. (SCIENCE and SOCIETY, 2018)
The article is devoted to the problems of conducting psychological studies among unorganized youth with the purpose of the development of their personal social self-improvement.
Keywords: unorganized youth; development of social activity; psychological research; factors of the study‘s results; wide community‘s care